Valor nutricional de silagens de resíduos da agroindústria da cana-de-açúcar e da mandioca avaliado em ovinos - Gargantini, Odnei Francisco (2013)
In this work, two experiments were conducted, aiming at studying the effects of the addition of sundried cassava peel and cassava bran to the silage of sugarcane tip, inters of qualitative aspects, intake and digestibility. The first experiment consisted of36 silos, to which crushed sugarcane tip was added, mixed with sundried cassava peeler with cassava bran at the levels of 0, 5, 10, 15 and 20 % of natural matter. The silos were weighted at closure and after 60 days of fermentation, when they were opened for evaluation of the gaseous and effluents losses, as well as for taking samples to determine pH and chemical composition. The values of dry matter (DM), crude protein(CP), neutral detergent fiber (NDF), acid detergent fiber (ADF), ethereal extract (EE),mineral matter (MM) and total digestible nutrients (TDN) were determined and differences were observed among treatments for all variables except for crude protein. The pH and effluent losses were not affected, although the gas losses were lower when the additive was sundried cassava peel. In the second experiment 24 Santa Inez/Dorper crossbred sheep were used, with an average weight of 29.4 ± 2.4 kg, divided into four treatments of six repetitions each, housed in metabolic cages with private feeders and drinkers. After an adaptation period of 10 days, the experimental phase of five days started, when all the food supplies and remains were weighted, faces and urine collected and weighed daily, and partial samples were obtained for determining digestibility. Two kinds of silage were produced: sugarcane tip with 20% sundried cassava peel (SCT + 20% DCP) and sugarcane tip with 18% cassava bran (SCT + 18%CBS). The proposed treatments were: 100% (SCT + 18% CBS); 67% (SCT + 18%CBS): 33% (SCT + 20% DCP); 33% (SCT + 18% CBS): 67% (SCT + 20% DCP); and100% (SPC+ 20% DCP) as forage. The concentrate, based on corn and soybean bran and mineral mixture for sheep had 23.0% crude protein and 85.0% total digestible nutrients, supplied at the ratio of 80% forage: 20% concentrate in order to maintain weight. We calculated the intake and digestibility of dry matter (DM), organic matter(OM), crude protein (CP), neutral detergent fiber (NDF), acid detergent fiber (ADF),total carbohydrates (TCHO), nonstructural carbohydrates (NSC), digestible energy (DE)in Mcal/day and nitrogen balance, with significant differences among treatments for intake of ADF and NDF, EE and NSC. The digestibility did not differ for any of the analyzed variables. Nitrogen balance was negative and significant for the animals treated with 100% tip sugarcane silage with cassava bran compared to the other treatments.